Identification of osteopontin as a urinary biomarker for autosomal dominant polycystic kidney disease progression - Hyunsuk Kim; Jinmo Sung; Ju Young Bae; Poongyeon Lee; Yun Kyu Oh; Hyunho Kim (The Korean Society of Nephrology, 2022)
Background Autosomal dominant polycystic kidney disease (ADPKD), one of the most common human monogenic diseases, is characterized by the presence of numerous fluid-filled renal cysts and is a leading cause of end-stage renal disease (ESRD). Urinary biomarkers may be useful for predicting the variable course of ADPKD progression from cyst growth to ESRD. Methods To identify candidate urinary biomarkers of ADPKD progression, we used CRISPR/Cas9 genome editing to generate porcine fibroblasts with mono- and biallelic ADPKD gene knockout (PKD2+/- and PKD2-/-, respectively). We then performed RNA-sequencing analysis on these cells. Results Levels of osteopontin (OPN), which is expressed by renal epithelial tubular cells and excreted into urine, were reduced in PKD2-/- cells but not in PKD2+/- cells. OPN levels were also reduced in the renal cyst cells of ADPKD patients. Next, we investigated whether OPN excretion was decreased in patients with ADPKD via enzyme-linked immunosorbent assay. OPN levels excreted into renal cyst cell culture media and urine from ADPKD patients were decreased. To investigate whether OPN can predict the rate of ADPKD progression, we compared urinary excretion of OPN in ADPKD patients with slow progression and those with rapid progression. Those with rapid progression had an estimated glomerular filtration rate of >60 mL/min/1.73 m2. Urinary OPN excretion levels were lower in rapid progressors than in slow progressors. Conclusion These findings suggest that OPN is a useful urinary biomarker for predicting ADPKD progression.